A Portable Nanogonal Rotating Hut for Observational Astronomy Activities in Schools and Colleges - Ratna, Ved (SCHOOL SCIENCE, 2013)
The appearance of Halley’s Comet in 1985 has aroused much interest in observational astronomy activities among school and college students in India. However, lack of proper guidance materials and facilities has been one of the major constraints to sustain this interest. Thus, there is an urgent need for providing necessary facilities for observing the night sky within the school/college premises or at another suitable venue. The proposed observation hut would not only fulfil this requirement but would also provide scope for conducting many activities based on astronomical observations. The salient features of the observation hut are: (i) preventing any health hazard to children from cold winds, and (ii) preventing vibration of the telescope caused by wind, in case its stand is not strong enough. This need is particularly important in Northern India. It is because that the proper season when the sky has minimum dust and clouds and when children also have time for co-curricular activities is after the rains, that is, from October to January, which is also the coldest part of the year